ANALISIS PEMASARAN DAN STRATEGI PENGEMBANGAN USAHATANI UBI KAYU DI KELURAHAN BALAI RAJA KECAMATAN PINGGIR KABUPATEN BENGKALIS PROVINSI RIAU - Rian Saputra; Fahrial (DINAMIKA PERTANIAN, 2021)
Balai Raja Village is one of the centers of cassava production in Pinggir District of Bengkalis Regency in Riau Province with production of 35 tons/ha. This research aims to find out and analyze the characteristics of farmers and traders of cassava, the marketing channels and institutions, marketing costs, marketing margin, marketing profits, farmer's share, and marketing efficiency of cassava farm business, and the cassava farming business development strategy. This study was used survey method during for 6 (six) months from July to December 2020. The results showed that the farmers was still productive life, the level of education of farmers was relatively low, namely junior high school graduation, the average length of experience was 4 years, and the number of farmers' families was 3 people. The average age of cassava traders was still productive life, the level of education of trader was relatively high, namely high school graduation, the average experience was 5 years, and the number of family member was 3 people. The marketing channel had only 1 marketing channel, namely farmer-trader - tapioca factory. Marketing cost was IDR 155/kg, marketing margin was IDR 200/kg, marketing net margin was IDR 45/kg, farmer's share was 75%. Marketing efficiency was 19.37%. The results of the analysis of the cassava farming business development strategy in the village of Pinggir district of Bengkalis Regency was in quadrant 1, namely the S-O. The alternative strategy obtained was based on the S-O strategy, namely the availability of land and skilled labor. It can meet the increasing demand for cassava production. By using superior wood seedlings and government support in providing extension, it can be expanded due to the development of cassava processing industry.